Physicians’ attitudes towards secondary use of clinical data for biomedical research purposes in Germany: results of a quantitative survey - Köngeter, Anja; Schickhardt, Christoph; Jungkunz, Martin; Mehlis, Katja; Winkler, Eva C. (PLOS ONE, 2024)
Background For biomedical data-driven research purposes, secondary use of clinical data carries great but largely untapped potential. Physicians’ attitudes and their needs towards secondary data use are essential to inform its practical and ethically sound implementation but are currently understudied. Objective Therefore, the objectives of the study are to assess physicians’ (i) general attitudes and concerns, (ii) willingness to adapt workflows and to make data available for secondary use, (iii) group-specific conditions toward implementation of secondary use and associated concerns of physician-scientists and purely clinical physicians. Methods We developed an online survey based on a literature review and an expert interview study. Physicians in private practice and at two large German university hospitals were surveyed from May 2021 until January 2022. Results In total, 446 physicians participated in the survey. 96% [380/397] of all physicians reported a positive attitude towards secondary use; 87% [31/397] are in-principle willing to support secondary use of clinical data along with a small proportion of physicians with fundamental reservations. Secondly, the most important conditions for adapting workflows were funding of additional time and effort for research-adequate documentation (71% [286/390]) and the most important condition for providing patients’ clinical data was reliable protection of patients’ privacy (67% [254/382]). Thirdly, physician-scientists were more likely than purely clinical physicians to request additional funding for research-adequate documentation as a precondition for support (83% vs 69%, P = .002) and the privilege to conduct research with their own patients’ clinical data before other researchers are allowed to (43% vs 11%, P < .001); while purely clinical physicians more frequently require reliable protection of patient privacy (76% vs 62%, P = .007) and monetary compensation (45% vs 25%, P < .001). Conclusion Since this study presents high in-principle willingness of physicians to support secondary use along with little general concerns, it seems essential to address physicians’ group-specific conditions toward secondary use in order to gain their support.
Gesehen am 19.06.2024